Household bargaining, pension contributions and retirement expectations: Evidence from the German Panel on Household Finances - Inês Fernandes; Tobias Schmidt (Deutsche Bundesbank, 2021)
In this paper, we study the relationship between intrahousehold bargaining styles, bar-gaining power and individual pension contributions and expected standard of living in retirement, using microdata from the German Panel on Household Finances (PHF) survey. The paper builds on a theoretical framework that predicts non-cooperative (cooperative) households to have lower (higher) expected standards of living in retirement, due to the uncertainty regarding intrahousehold resource sharing. The empirical results suggest that household bargaining is significantly correlated with individual retirement-related behaviour and expectations, with gender differences. Cooperative partners expect higher standards of living in retirement, relative to non-cooperative ones, because they may insure againstold-age poverty by pooling and redistributing personal and household resources amongst each other in retirement. Finally, our data indicate that intracouple information sharing and altruism may mediate the relationship between household decision-making and individual contributions to private pension plans, especially in non-cooperative households.
Keywords: D12; D14; G51; 330; Intrahousehold bargaining; Intrahousehold information sharing; Gender; House-hold finance; Private pension plans; Retirement expectations; Altruism; Panel on HouseholdFinances